Two Roads Forward for Labor: The AFL--CIO's New Agenda. - LICHTENSTEIN, NELSON (Dissent (0012-3846))
The author comments on the strategic initiative launched by the American Federation of Labor and Congress of Industrial Organizations (AFL-CIO) against the administration of U.S. President Barack Obama in 2010. Topics covered include the group's opposition to the Employee Free Choice Act, labor membership law and the high unemployment rate in the country. Also mentioned are the defeat of trade union movements, vindication of social policy liberalism and the labor sector campaign launched by former U.S. President Bill Clinton in 1996.